Inoculation theory revisited: reinterpretations, extensions, and new directions - Feng, Guangchao Charles (Frontiers in Communication, 2025)
Inoculation theory offers a unique perspective on how beliefs can be fortified against persuasive attacks. However, several aspects of the theory warrant further exploration and reinterpretation, particularly its analogies with immunology. The paper aims to broaden the theory’s boundary conditions by delving into thought-provoking analogies between immunology and persuasion. The author redefines multiple key concepts within inoculation theory and addresses a range of existing issues associated with classic inoculation theory, including the distinction between passive and active defense and addressing “infected” people and “allergy” with therapeutic inoculation. The paper concludes by proposing future research directions that include exploring diverse, especially mRNA forms of “inoculation” and formulating a series of conceptual propositions.